PEMODELAN RISIKO KERUGIAN AKIBAT GEMPA BUMI: STUDI KASUS WILAYAH M7 MEGATHRUST INDONESIA - Dea Permata Sari; Azizah Azizah (Universitas Muhammadiyah Surabaya, 2025)
Indonesia faces a high risk of earthquakes due to its location in the megathrust zone, including the M7 Sunda Strait segment, which has the potential for high-magnitude earthquakes. This study aims to model and estimate potential financial losses caused by earthquakes using the Earthquake Catastrophe Model, which consists of four main modules: hazard, inventory, vulnerability, and loss. Earthquake data obtained from the official USGS website were processed using the declustering method to extract mainshock events. The Generalized Pareto Distribution was then applied to model earthquake magnitudes, while spectral acceleration values were calculated using the attenuation function of Zhao et al. (2006). A Monte Carlo simulation was conducted to generate stochastic earthquake events and to simulate total aggregate loss (S), which was subsequently modeled using the Bernoulli-Lognormal Two-Part Model. The results indicate that, with a 95% confidence level, the estimated financial loss due to an earthquake in the M7 megathrust zone of the Sunda Strait will not exceed IDR 298 billion. These findings are expected to serve as a foundation for disaster risk mitigation planning and insurance financing schemes for local governments and the financial sector in Indonesia.